ORTEGA LEYENDO A DILTHEY, E IDEAS SOBRE LA VIDA (Res Publica. Revista de Historia de las Ideas Políticas, 2009)
This essay explores the affinities between the Orteguian concept of «living consciousness,» as expressed in the 1933 essay «Guillermo Dilthey y la idea de la vida,» with Mussoliniʼs fascist language on the New State and with the Roman notion of imperium.